Economic and accounting issues of the transformation of limited liability companies into cooperative entities - Emilio Mauleón Méndez (AECOOP Escuela de Estudios Cooperativos, 2019)
The Companies Structural Modifications Act (Ley 3/2009 sobre modificaciones estructurales de las sociedades mercantiles) has boosted the processes of companies’ transformation, since it has unified the regulatory dispersion existing up to that moment and has facilitated the transformation processes by law. In the present paper we will deepen in the processes of socially responsible transformation, in particular, in the transformation of a limited-liability company towards a cooperative. This transformation implies a change of attitude of the partner towards the company in which he participates. The partner changes from being a simple investor to becoming involved in the cooperative activity as the main actor of it. It can also affect the responsibilities of the partners and the structure of share capital. This and other substantial changes that will occur in the legal and economic framework of the entity that is transformed will bring consequences in the accounting plane. Therefore, once the economic and legal aspects of the transformation of the limited-liability company into a cooperative are detailed, we will analyze the accounting peculiarities that derive from the operation. We rely both on the substantive regulations of the two entities, as well as on current accounting regulations, specifically the General Accounting Plan, the Rules on accounting aspects of cooperative societies and the draft Resolution of the Institute of Accounting and Accounts Auditing that affects to these operations. We will analyze the singularities that will affect the balance of transformation, the consequences on the share capital of the partner separation who is not satisfied with the transformation, the accounting reclassification of the share capital and the accounting particularities that concern other items of capital resources from the limited-liability company to become a cooperative, such as reserve funds.